Genetic Identification of Edible Bird’s Nest in Thailand Based on ARMS-PCR - Lv, Dongyong; Fan, Yaohua; Zhong, Wanhua; Lonan, Piyanuch; Liu, Kunfeng; Wu, Maoyong; Wu, Yina; Liang, Yueliang; Lai, Xiaoping; Li, Geng; Yu, Liangwen (Frontiers in Genetics, 2021)
Edible bird’s nest (EBN) is a popular delicacy in the Asian Pacific region originating from Indonesia, Malaysia, Thailand and Vietnam, which consist of various potential medicine value in Traditional Chinese Medicine (TCM). Thailand is one of the main exporters of EBN. However, the genetic information of EBN, a key part of molecular biology, has yet to be reported in Thailand. It is necessary to explore the genetic information of EBN in Thailand based on a quick and simple method to help protect the rights and interests of consumers. This research aimed to systematically evaluate different methods of extracting EBN DNA to improve the efficiency of the analysis of cytochrome b (Cytb) and NADH dehydrogenase subunit 2 (ND2) gene sequences, the establishment of phylogenetic trees, and the genetic information of EBN in Thailand. Additionally, we aimed to develop a quick and simple method for identifying EBN from different species based on the genetic information and amplification-refractory mutation system PCR (ARMS-PCR). By comparing the four methods (cetyltrimethylammonium bromide (CTAB), sodium dodecyl sulfate (SDS), kit and guanidinium isothiocyanate methods) for EBN extraction, we found that the guanidinium isothiocyanate method was the optimal extraction method. Phylogenetic trees generated on the basis of Cytb and ND2 gene analyses showed that 26 samples of house EBN and 4 samples of cave EBN came from Aerodramus fuciphagus and Aerodramus maximus, respectively. In addition, to distinguish different samples from different species of Apodiformes, we designed 4 polymerase chain reaction (PCR) amplification primers based on the ND2 gene sequences of Aerodramus fuciphagus and Aerodramus maximus. The ARMS-PCR results showed band lengths for Aerodramus fuciphagus EBN of 533 bp, 402 bp, and 201 bp, while those for Aerodramus maximus EBN were 463 bp, 317 bp, and 201 bp. Collectively, the results showed that ARMS-PCR is a fast and simple method for the genetic identification of EBN based on designing specific original identification primers.